Modelling of sensored speed control of BLDC motor using MATLAB/SIMULINK - Basim Alsayid; Wael A. Salah; Yazeed Alawneh (Institute of Advanced Engineering and Science, 2019)
Recent developments in the field of magnetic materials and power electronics, along with the availability of cheap powerful processors, have increased the adoption of brushless direct current (BLDC) motors for various applications, such as in home appliances as well as in automotive, aerospace, and medical industries. The wide adoption of this motor is due to its many advantages over other types of motors, such as high efficiency, high dynamic response, long operating life, relatively quiet operation, and higher speed ranges. This paper presents a simulation of digital sensor control of permanent magnet BLDC motor speed using the MATLAB/SIMULINK environment. A closed loop speed control was developed, and different tests were conducted to evaluate the validity of the control algorithms. Results confirm the satisfactory operation of the proposed control algorithms.